Bioavailability of lysine from hydroxymethyl lysine - E.A. Elwakeel; Evan C. Titgemeyer; D.W. Brake; A.M. Nour (Kansas Agricultural Experiment Station Research Reports, 2010)
Twelve mature sheep were used as a ruminant model to estimate the bioavailability of lysine in hydroxymethyl lysine (HML) compared with a commercial product of rumen-protected lysine (RPL; LysiPEARL, Kemin Industries, Inc.) with known availability. The sheep were fed a diet with a forage to concentrate ratio similar to that of dairy diets. Following a control period in which plasma lysine was measured when sheep received no supplemental lysine, the sheep were provided 2 of 4 treatments during periods 2 and 3; treatments included RPL to provide 3 or 6 g/day of available lysine (actual amounts of product provided were based on the manufacturer's data related to ruminal escape and intestinal availability) and 3 or 6 g/day of lysine provided as HML. Blood samples were collected at the end of each feeding period at 3 hours after feeding. Both HML and RPL significantly increased plasma lysine concentrations. By comparison with plasma lysine concentrations when known amounts of bioavailable lysine were provided as RPL, the bioavailability of lysine in HML was estimated to be 94%. Results indicate that HML may be an effective means of supplementing lysine to dairy cattle.; Dairy Day, 2010, Kansas State University, Manhattan, KS, 2010; Dairy Research, 2010 is known as Dairy Day, 2010
Keywords: Dairy Day; 2010; Kansas Agricultural Experiment Station contribution; no. 11-129-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 1039; Dairy; Lysine bioavailability; Rumen-protected lysine; Sheep